(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
This paper explores an experiential process that the authors created for a workshop at the 2021 SEA Conference. It interprets our experience of the process and the participants’ contributions by means of an informal poetising hermeneutic borrowed from van Manen, and invites readers to imagine possibilities for writing and therapy.